Role of Women in Rural Development - DEVI, TRISHNASHREE (International Journal of Advanced Science and Technology, 2019)
Woman is no longer confined to the role of home maker rather her roles are redefined in this new millennium. Women have been contributing to economic productivity since the dawn of human history. The rural women have a long tradition of doing various economic and productive activities although their role has been visualized as a passive one. In this paper an attempt has make to examine the status of women in rural areas and their contribution of women in rural development. Moreover, this paper will illustrate women contribution in economic development of rural areas. It also discuss some constraints faced by women in rural development. Last but not the least this paper tries to give some suggestions for empowers and increases the role of women in rural development.